2008
DOI: 10.1111/j.1524-4725.2008.34283.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells and Their Secretory Factors as a Promising Therapy for Skin Aging

Abstract: ADSCs and their secretory factors show promise for application in cosmetic dermatology, especially in the treatment of skin aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 6 publications
3
102
0
2
Order By: Relevance
“…Another is a paracrine effect on surviving, resident cells induced by the secretion of cytokines, growth factors, and other cellular factors. Evidence has also indicated that the regenerative effects are mediated by angiogenic, antiapoptotic, and growth factors secreted by ASCs [68,69,[127][128][129][130]. ASCs migrated into an injured or diseased organ or tissue may secrete these factors that stimulate recovery in a paracrine manner.…”
Section: Clinical Trialsmentioning
confidence: 96%
“…Another is a paracrine effect on surviving, resident cells induced by the secretion of cytokines, growth factors, and other cellular factors. Evidence has also indicated that the regenerative effects are mediated by angiogenic, antiapoptotic, and growth factors secreted by ASCs [68,69,[127][128][129][130]. ASCs migrated into an injured or diseased organ or tissue may secrete these factors that stimulate recovery in a paracrine manner.…”
Section: Clinical Trialsmentioning
confidence: 96%
“…27 Recently, the production and secretion of growth factors has been identified as essential functions of adipose stem cells, and diverse rejuvenation effects of adipose stem cells on skin have been demonstrated. 28,29 For example, they demonstrated that the cultured medium from adipose stem cells stimulated both collagen synthesis and migration of dermal fibroblasts during the wound-healing process. 30 The cultured medium of adipose stem cells also inhibited melanogenesis by down-regulation of tyrosinase and tyrosinase-related protein-1 (TRP-1) expression in the B16 melanoma cells.…”
Section: Discussionmentioning
confidence: 98%
“…40 These effects have been evaluated in a porcine model, demonstrated by measuring growth factor production and collagen synthesis after injection of ADRCs. 40 Potentially, ADRCs may exert beneficial effects on angiogenesis and collagen production and potentially reduce aging and accumulation of abnormal elastin. In addition, mesotherapeutic applications of ADRCs have been anecdotally shown to improve hair growth in women with androgenetic alopecia (Fig.…”
Section: Mesotherapeutic Applicationsmentioning
confidence: 99%